Symbolic values in Peyami Safa's novel, "Fatih-Harbiye" - Şahin, Veysel (Ahmet Yesevi University, 2010)
Peyami Safa always wanted to become a part of the world without leaving our own values and to turn these values into national reflexes. His novel, titled "Fatih-Harbiye" is a universe of symbolic conflicts based on these thoughts. "Fatih-Harbiye" brings together traditional and universal values through the language of symbols, and it is a mirror reflecting Turkish spirit and customs. The spiritual changes and conversions Neriman experiences are dealt with in the flow of time and place through the language of symbols and associations. In this way, the author finds what he is looking for within the conceptual values of expression and turns the visual into traditional symbolism by giving new meaning to it through the language of symbols. © Ahmet Yesevi University Board of Trustees.
Peyami Safa'nın "Fatih-Harbiye" adlı romanında Simgesel De?erler
Keywords: East-west; Fatih-harbiye; Home; Music; Neriman; Spirit; Şinasi; Tradition